PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK SKINTIFIC DI KALANGAN MAHASISWA UNIVERSITAS BUANA PERJUANGAN KARAWANG - Nabila Nur Hayati Fadhilah; Sungkono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aimls to analyze the influence of product quality on purchasing decisions for Skintific products amlong students at Buana Perjuangan University, Karawang. Product quality includes various aspects such as effectiveness, safety of use, and the ingredients used. This research uses quantitative mlethods with randoml samlpling techniques, involving students who have used Skintific Skincare products. Data was collected through surveys and analyzed using simlple linear regression. The research results show that product quality has a significant influence on students' purchasing decisions. This research provides insight into student preferences and purchasing behavior in the context of Skintific products, as well as the imlportance of product quality in influencing purchasing decisions.